Epitaxial Growth of PbSe Quantum Dots on MoS2 Nanosheets and their Near‐Infrared Photoresponse. (14th July 2014) - Schornbaum, Julia; Winter, Benjamin; Schießl, Stefan P.; Gannott, Florentina; Katsukis, Georgios; Guldi, Dirk M.; Spiecker, Erdmann; Zaumseil, Jana
<x xml:space="preserve">Abstract</x> A facile one‐pot synthesis of hybrid materials consisting of PbSe quantum dots (QDs) that grow epitaxially on MoS2 nanoflakes resulting in three equivalent orientation variants of the PbSe QDs with respect to the MoS2 lattice is demonstrated. The epitaxial growth and cross‐sectional high‐resolution transmission electron microscopy (HRTEM) investigations verify a direct and linker‐free contact between the quantum dots and the transition metal dichalcogenide (TMD) nanoflakes, while maintaining surface passivation of the PbSe with oleic acid ligands on the outside. Solution‐processed photodetectors based on PbSe‐MoS2 hybrids exhibit stable photoconduction when illuminated with near‐IR light (wavelength > 1200 nm) without any laborious ligand‐exchange steps. Flexible devices fabricated on polyethylene terephthalate (PET) substrates show excellent stability upon repeated bending. These hybrid materials are air‐stable and solution‐processable at low temperatures and thus promising for low‐cost flexible near‐IR photodetectors.